A Randomized Controlled Clinical Trial Comparing Clinical and Radiographic Success Rates of MTA and rhBMP2 in Pulpotomy of Primary Teeth - Nosrat Nourbakhsh; Sanaz Ziaei; Hesam Panahi; Nahad Sedaghat; Amirhossein Behnia (Frontiers in Dentistry, 2024)
Objectives: In an ideal pulpotomy, the radicular pulp remains vital, healthy, and fully encased within an odontoblastic layer. Mineral trioxide aggregate (MTA) and bone morphogenetic proteins (BMPs) have been suggested to facilitate this outcome. We aimed to compare the clinical and radiographic failure and success rates of MTA and rhBMP2 as pulpotomy medicaments.